Pengembangan Budaya Literasi Masyarakat Desa Nekmese melalui Integrasi Pojok Literasi dan Rumah Baca Digital - Yefris Adrianto Selan; Migdes Christianto Kause; Serlinia Rambu Anawoli (STKIP AL HIKMAH SURABAYA, 2026)
This study aims to analyze the development of Literacy Corners and a Digital Reading House as an effort to foster a reading culture among the residents of Nekmese Village. The study employed a qualitative descriptive approach, with data collected through observations, interviews, documentation, and questionnaires used as supporting data. The findings indicate that the establishment of four Literacy Corners and one Digital Reading House improved community access to reading resources and generated significant social and educational impacts. Children demonstrated improved reading skills and greater confidence in expressing themselves, adolescents showed enhanced information literacy and digital literacy, while parents developed greater awareness of the importance of reading culture for children's development. The findings further reveal that the integration of physical literacy facilities and digital learning resources, supported by active community participation, contributed to the development of a sustainable community-based literacy ecosystem for fostering a reading culture in Nekmese Village.